Pengetahuan Ibu Tentang Perkembangan Motorik Kasar pada Balita usia 3-4 Tahun - Darah Ifalahma; Nur Hikmah (Jurnal Infokes, 2020)
The toddler period is called the golden period because it has enormous potential to optimize all aspects of development. The development of each child will go through stages that take place sequentially, continuously and within a certain tempo. By understanding the stages of a child's development, parents will be able to assess the child's development according to generally accepted standards. If a child is observed who has developmental delays, parents can act immediately. Conversely, parents can also prepare children by providing stimulation in accordance with the child's abilities at a certain age. Knowledge and awareness of parents is very necessary to monitor and stimulate children's development. The research objective was to determine the knowledge of mothers about gross motor development in children aged 3-4 years.This research design uses descriptive research method. The instrument used was a questionnaire. The sample of this research is mothers who have children under five in Playgroup Cepaka 2 Semanggi Surakarta with a total of 35 respondents. The sampling technique is nonprobability sampling with saturated samples. Data analysis used univariate analysis.The results of the study were the level of maternal knowledge about gross motor development in toddlers. Overall, the respondents had good knowledge, 2 people (5.7%), 19 people (54.3%) with sufficient knowledge, and 14 people with less knowledge (40.0%).The conclusion of the mother's knowledge about gross motor development in toddlers is in the moderate category. Suggestions for mothers are expected to increase awareness of the importance of increasing knowledge about gross motor development in toddlers.